Effect of Training and Development on Service Delivery in Public Health Institutions of Western Kenya Region - Maurice Erambo; Eglay Tuvulla Tsuma; Willis Ingabo Otuya (Sustainable Business and Society in Emerging Economies)
Purpose: To assess the effect of training and development on service delivery in public health institutions of Western Kenya Region